2017
DOI: 10.1177/1474704917740466
|View full text |Cite
|
Sign up to set email alerts
|

Hadza Men With Lower Voice Pitch Have a Better Hunting Reputation

Abstract: Previous research with hunter-gatherers has found that women perceive men with voices manipulated to be lower in pitch to be better hunters, and men perceive women with lower pitch to be better gatherers. Here, we test if actual voice pitch is associated with hunting and gathering reputations in men and women, respectively. We find that voice pitch does relate to foraging reputation in men, but not in women, with better hunters having a lower voice pitch. In addition, we find that the previously documented rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 100 publications
(169 reference statements)
4
35
1
Order By: Relevance
“…Our analyses revealed no clear evidence that stronger individuals had more masculine voices. These results are consistent with other work finding similar null results (Sell et al, ; Smith et al, ), suggesting that previously reported positive correlations between arm strength and sexually dimorphic vocal characteristics (Puts et al, ) may not be robust. Our null results are also consistent with recent work suggesting that voices may not necessarily be a valid cue of men's threat potential (see also Han et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our analyses revealed no clear evidence that stronger individuals had more masculine voices. These results are consistent with other work finding similar null results (Sell et al, ; Smith et al, ), suggesting that previously reported positive correlations between arm strength and sexually dimorphic vocal characteristics (Puts et al, ) may not be robust. Our null results are also consistent with recent work suggesting that voices may not necessarily be a valid cue of men's threat potential (see also Han et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Although the speech samples we used are similar to those employed in previous research on this topic, stronger relationships between strength and vocal characteristics might occur using less neutral vocalizations (eg, the type of vocalizations made during direct competition), if individuals exaggerate existing (but otherwise subtle) vocal cues of strength when competing. Nonetheless, we note here that several studies have now found no significant correlations between strength and vocal masculinity in men (Kordsmeyer, Hunt, Puts, Ostner, & Penke, ; Sell et al, ; Smith et al, ) and the significant correlations reported by Puts et al () were both inconsistent across samples and would not have been significant if corrected for multiple comparisons. Collectively, these points may indicate the correlations reported in Puts et al () might be false positives.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Several studies have tried to find a link between voice pitch and physical strength, but the results are weak and do not typically replicate. Three ` independent lab groups were unable to find any link between voice pitch and physical strength measures among adults (Han et al, 2017;Sell et al, 2010;Smith, Olkhov, Puts, & Apicella, 2017). Out of several published samples on adults, only one reports that voice pitch is negatively related to physical strength (Puts, Apicella, & Cárdenas, 2012), however, these results were weak and only significant when not controlling for multiple comparisons (Bakker, Hartgerink, Wicherts, & van der Maas, 2016).…”
Section: Pitchmentioning
confidence: 92%
“…The entire process was then repeated for each trait. The Hadza have previously done this task multiple times HADZA DISAGREE ON MORAL CHARACTER 9 to rank campmates on hunting ability (Apicella, 2014;Smith, Olkhov, Puts, & Apicella, 2017;Stibbard-Hawkes, Attenborough, & Marlowe, 2018).…”
Section: Methodsmentioning
confidence: 99%